PEMBENTUKAN CITRA DIRI ANAK BURUH MIGRAN PEREMPUAN ASAL KOTA DUMAI - Rahmah Husna Yana; Irma Juraida; Triyanto Triyanto (Jurnal Community, 2019)
Abstract*This research aims to find out how the formation of the self-image of female migrant worker children from Dumai city with a research analysis using the looking glass self theory of Charles Horton Cooley who argues that self-image is not born just like that but through three stages, namely, perception, interpretation, and the response. The method used in this research is descriptive qualitative method. Field data obtained by interview and observation techniques. Data analysis uses qualitative analysis, which is an analysis that provides in-depth descriptions and conclusions that are consistent with the topic and purpose of the study. The data analysis stage is the data reduction stage, the data presentation stage and the data analysis stage. The results show that parenting patterns and social interactions between children and surrogate parents greatly influence the formation of the child's self image.Keywords: Self-Image, Children, Female Migrant Workers